The business of shipping - Lane, C. Kendall (Cornell Maritime Press, 1973)
Describing and analyzing the shipping business as it exists today, the book is intended for executives and others who may be specialists in one branch of the business, but only marginally knowledgeable about its other aspects. It will also familiarize newcomers with the many facets of the shipping enterprise. Although not written as a textbook, it could be used as a basic resource for any marine transportation course...